A study on the effectiveness of the Malaysian Anticorruption Commission 2009 / Muhammad Aizat Afifi Zainuddin … [et al.] - Zainuddin, Muhammad Aizat Afifi; Shahruddin, Mohammed Azmi; Bahtiar, Mohd Syafiq; Ibrahim, Mohamad Helmi (2013)
Despite fast changing ways of life, the crime namely 'corruption' has been hesitantly recognized either by the society or law in Malaysia. Most researchers and scholars believe that though the era has changes in their lives, in the case of corruption, most people still not aware of this sinful crime or just pretend do not know. However, it must be noted that the number of corruption level in Malaysia has been increasing over the years and it like the disease in our society. The lack in Malaysia anti corruption law, enforcement and political has caused the corruption problems to arose. As corruption happen among the society, it would be necessary for the government to look into this matter and assist them in any possible way especially in improving the law. Therefore, this research looks into the issue of the recent anti corruption law in Malaysia particularly the loopholes in it. This research also compares the situation in other countries such as Hong Kong, Singapore and United Kingdom in order to find the best anti corruption law to adapt in Malaysian anti corruption law and also to enhance the current law.